Extending the UTAUT model to understand the barriers towards SME digitalization in the Czech Republic - Kwarteng , Michael; Plata, Diego; Ratilla , Mark; Novak , Petr; Zlamal, Lukas (Serbian Journal of Management, 2022)
Digitalization has been identified as a core growth driver for small and medium enterprises (SMEs) in this digital era. This study investigates the drivers and barriers aligned with the tendency of owner-managers of SMEs to adopt digitalization. A conceptual framework is developed that extends the unified theory of acceptance and technology (UTAUT) with an anxiety-digitalized environment as a moderating factor of SME owner-managers’ intention to adopt digitalization. A quantitative methodology is used to gauge responses from 89 respondents (owner-managers). Additionally, the variance-based structural equation modelling approach (PLS-SEM) is used to analyse and validate the proposed model. Results show that attitude positively mediates the relationship between performance expectancy and intention to adopt digitalization. However, effort expectancy and facilitating conditions were found to negatively influence attitude and intention to adopt digitalization. On the contrary, the results obtained did not confirm the significance of an anxiety-digitalized environment in moderation analyses. Consequently, the overall structural model accounted for 51.1% of the variance in the intention to adopt digitalization among SMEs. This study has theoretically and practically contributed to understanding owner-managers’ intent to adopt digitalization of SMEs in the Czech Republic.